Ответы и объяснения

2012-12-14T13:10:38+04:00

 

 1) log(3)5*log(4)9*log(5)2=log(3)5*log(3)9*log(3(2)/log(3)4*log(3)5=2*log(3(2)/log(3)4= 
2*log(2)2*log(2)3/log(2)3*log(2)4=2*1/2=1 

2) log(sqrt(6)3*log(3)36+log(sqrt(3)*log(4)81= 
log(3)3*log(3)36/log(3)sqrt(6)*log(3)3+log(3)8*log(3)81/log(3)sqrt(3)*log(3)4= 
log(3)36/log(3)sqrt(6)+4*log(3)8/0,5*log(3)4= 
log(2)36*log(2)3/log(2)3*log(2)sqrt(6)+8*log(2)8*log(2)3/log(2)3*log(2)4= 
log(2)36/log(2)sqrt(6)+8*log(2)8/log(2)4=2*log(2)6/0,5*log(2)6+24/2=4+12=16

2012-12-14T13:10:56+04:00